Phytochemical and Pharmacological Exploration of Cyperus articulatus as a Potential Source of Nutraceuticals and Drug Ingredients - Swain, Ayusman; Santhoshkannada, Aralakuppe Narayana; Prabakaran, Duraivadivel; Choudhir, Gourav; Puttaswamy, Hariprasad (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Cyperus articulatus rhizome has been used in folk medicine by different inhabitants belonging to tropical and subtropical regions. But its metabolite profile and potential pharmacological and food applications were hardly explored. Evaluation of biological activities of Cyperus articulatus metabolites was the objective of the present study. Materials and Methods: In vitro biological studies concerning radical scavenging, reducing activity, food (meat and β-carotene) protection, biomolecule (DNA and Protein) protection and Acetylcholinesterase inhibitory activity were carried out for the rhizome extracts. Chemical constituents of the bioactive rhizome extract were analyzed through HRLC-MS/MS. Results: The rhizome acetone extract showed the highest antioxidant activity and protected DNA and protein from degradation at the lowest concentrations compared to all the six different solvent extracts tested. It significantly inhibited β-carotene bleaching, controlled the TBARS values during meat oxidation and significantly inhibited the Acetylcholinesterase enzyme. The major compounds detected in HRLC-MS/MS were dihydroquercetin, mycophenolic acid, embelin, quercetrin, meptazinol, koparin-2-methyl ether, venpocentine along with other phenolics and polyhydroxy compounds. Conclusion: The study explored Cyperus articulatus rhizome as a pharmacologically important source for nutraceuticals and drug ingredients and suggested further safety and efficacy studies of the detected metabolites.
Keywords: Secondary metabolites; Food model; DNA protection; Enzyme inhibition; Dihydroquercetin